Multipolar Intuitionistic Fuzzy Positive Implicative Ideal in B-Algebras - Amigo, Royyan; Hidayat, Noor; Krisnawati, Vira Hari (Mathematics Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
In this paper, we start with the concept of B-algebras, commutative B-algebras and fuzzy ideal in B-algebras. We also study about multipolar intuitionistic fuzzy ideal. We explain the notion of multipolar intuitionistic fuzzy positive implicative ideal in B-algebras and some characterizes. In addition, we examine some theorems and proportions which contain the conditions for a multipolar intuitionistic fuzzy set become a multipolar intuitionistic fuzzy positive implicative ideal in B-algebras. One of the result is a multipolar intuitionistic fuzzy set (l,s) over commutative B-algebra X is a multipolar intuitionistic fuzzy positive implicative ideal (l,s) over commutative B-algebra X if and only if (x*y)*z=0 implies l(x)= Infl(y),l(z) and s(x) = Sups(y),s(z), for all x,y,z.